1984
DOI: 10.1063/1.1137821
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of H− beams from a magnetically filtered multicusp source

Abstract: H− ions produced by volume processes have been extracted from a multicusp source operated with a magnetic filter and accelerated to form a high-quality beam. It was found that the H− beam current increased almost linearly with the discharge current. An H− ion current density of 38 mA/cm2 was obtained with a discharge current of approximately 350 A. The accelerated beam was mass analyzed and the emittance of the H− component was measured. The electron component and the percentage of ion impurity in the extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Subsequently, H À is produced by dissociative electron attachment to rotationally/vibrationally excited H 2 as shown in Eq. (2). In the ion source chamber, it is advantageous to separate the plasma into two different regions of high and low electron temperature regions to enhance H À production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, H À is produced by dissociative electron attachment to rotationally/vibrationally excited H 2 as shown in Eq. (2). In the ion source chamber, it is advantageous to separate the plasma into two different regions of high and low electron temperature regions to enhance H À production.…”
Section: Introductionmentioning
confidence: 99%
“…In applications where a high-brightness beam of H À is required, the volume production process is preferred since the generated ion beam has been found to have lower emittance [2]. In the volume production process, H À is produced by a twostep process [3,4]:…”
Section: Introductionmentioning
confidence: 99%
“…As the produced H -can be easily destroyed by e f , the region where H 2v * are produced is geometrically separated from the region where H -are produced and extracted. An ion source plasma is usually separated into these two regions by inducing an external magnetic field [3], which is often called a "magnetic filter field." The region to produce H 2v * is called driver region, and the region to extract H -is called the extraction region.…”
Section: Introductionmentioning
confidence: 99%
“…6 Most recently, a small multicusp source has been fabricated and operated successfully to generate volume-produced H-ions. 7 From this new source, H-current densities as high as 240 mA/cm 2 1-IlII1-diam aperture. The increase in H:-output is mainly due to an increase in the source plasma density.…”
Section: Introductionmentioning
confidence: 99%
“…H-and 0-ions are used to generate efficient neutral beams with energies in excess of 150 keV.1 It has been demonstrated that volume-produced H-ions, extracted from a filter-equipped multicusp source can provide high quality Hbeams with sufficient current density (40 mA/cm 2 ) to be useful for both neutral beam heating of fusion plasmas and accelerator applications. 2 In order to produce this high H-current density, it was necessary to operate the source with a discharge current as high as 350 A.…”
Section: Introductionmentioning
confidence: 99%